Effects of Origami Pattern Crash Box and Rectangular Pattern Crash Box on The Modelling Of MPV Car Structure on Deformation - Kusyairi, Imam; Choiron, Moch. Agus; Irawan, Yudy Surya; Himawan, Helmy Mukti (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2018)
Crash box serves as a kinetic energy absorber during collision. It has a tube shape, which is located between bumper and chasis. The crash box design requires development in order to reduce buckling mode and obtain symmetry folding mechanism, so it will achieve greater energy absortion. The researchers find a method to reduce tension due to impact by providing dents in crash box geometry. This research observed origami pattern crash box design having dents functioned as pre-folded so that collapse mode can be predicted and stable. In this research, the crash box was modeled according to the size of bumper and chassis on the MPV car. Testing simulation was performed by modelling Impactor as rigid body and crash box as flexible. Fixed support was housted in the surface of rear side of the crash box. Simulation process was started from the impactor moving to supress crash box. This Impactor collision led to deformation on the crash box. Crash box material was AA7004-T7, it was modelled as bilinier isotropic hardening. Based on the research result, the addition of pre folded pattern is able to reduce impact force at the first impact and has stable characteristic as well as predictable collapse mode.